Changes in dietary pattern when including 700 g of salmon per week to patients with atherosclerotic heart disease. (June 2017) - Gharagozlian, Sedegheh; Hansen, Renate; Haugen, Margretha; Johansen, Odd; Seierstad, Sverre Ludvig; Seljeflot, Ingebjørg; Arnesen, Harald
Summary: Background and aims: Increased consumption of fish is associated with reduced risk of coronary heart disease (CHD). Therefore, we investigate whether an intervention with farmed salmon entailed changes in normal dietary pattern as well as in intake of other cardioprotective or proatherosclerotic foods. Methods: 60 patients with CHD were randomly assigned to three groups consuming approximately 700 g per week for 6 weeks of Atlantic salmon differently fed i.e.: 100% fish oil (FO), 100% rapeseed oil (RO) or 50% of each (FO/RO). Dietary habits were assessed at baseline and after the intervention period by using a validated food-frequency questionnaire. Blood samples were obtained pre- and post-intervention after an over-night fast. Results: Increasing salmon intake caused a significant reduction in intake of all meat, processed meat and other kinds of fish, i.e. processed and lean fish, carbohydrates and starch (all p < 0.001). Total intake of milk remained unchanged, whereas the sum of all dairy products was significantly reduced (all p < 0.01). A significant increase in total n -3 fatty acid, eicosapentaenoic acid, docosahexaenoic acid and n -3/ n -6 ratio in the total population was obtained, most prominent in the FO group. The intake of saturated fatty acids was moderately reduced ( p < 0.01). The total intake of fruit, berries and vegetables remained unchanged, but intake of boiled vegetables increased significantly. Conclusions: Including 700 g of salmon to the diet changed the patient's normal dietary pattern significantly, both intakes of food groups and nutrient. With regards to the recommended consumption of marine n -3 fatty acids for CHD patients, fillets from fish fed 100% FO were found to be the most beneficial.